Characteristics of Hypospadias Cases at the Arifin Achmad Riau General Hospital - Joko Pitoyo; Muhammad Adan Yashar; Fahreza Syukri (Future Science, 2022)
Cases of hypospadias were found to vary in specific periods, but There is currently no data on hypospadias cases handled at the Arifin Achmad Riau general hospital. Therefore, the researchers conducted this study which is a descriptive retrospective study, by taking data from the medical records of hypospadias patients at Arifin Achmad Hospital, Riau Province, for four years from 2017 to 2021. The data taken included the patient's age, type of hypospadias, whether there is a penis chordee, and the surgical technique performed. From the results of this study, there were 60 cases of hypospadias for four years (2017-2021) with a mean age of 11.73 (plus minus 11). Of the 60 hypospadias cases, 8 cases of anterior hypospadias (13.3%) were found. There were 26 cases (43.33%) of middle hypospadias. There were 24 cases (40%) of posterior hypospadias. There were 2 cases with cripples hypospadias (3.34%). The surgical technique performed is also different for each type. The surgical methods performed include Urethroplasty with Mathieu technique in 8 cases (13.33%), Urethroplasty with TIP technique in 9 (15%), Urethroplasty with SLAM technique in 16 (26,66%), Stage urethroplasty in 17 (28,33%), other procedure in 10 (16,67%). Prospective studies need to be carried out to compare the success rates of each surgical procedure related to the type of hypospadias and the degree of chordee.